Iowa farm in your pocket : a beginner's guide - Murray, Kirk (Bur Oak guide., 2010)
Newcomers to Iowa are always amazed at the yearly changes in the heights of fields. The landscape expands from ground level to ten feet tall and back again every year: from frozen bare ground in winter to light green sprouts in late spring to dark green corn in late summer to acre upon acre of dry cornstalks at harvest time. Slow and unwieldy machines take up more than their share of the roads, clouds of black or yellow dust cover the fields in spring and fall, pigs (or are they hogs?) in various colors look out from fences, huge tractors with complicated add-ons lumber through the fields, shiny silos linked with tentacles tower above tidy white farmhouses dwarfed by huge red barns. What are the names of all these animals and crops and buildings and machines? As an introduction to the practical magic of Iowa farmscapes, Iowa Farm in Your Pocket won't tell you everything you should know to be a true Iowan, but it will tell you enough that you can survive a day at the state fair without embarrassing yourself. Iowa ranks first in the U.S. in the number of hogs, egg layers, and pullets and in the production of corn and soybeans. Yes, the number of farms is shrinking, and their size is increasing. Yes, most Iowans now live in towns, compared to a hundred years ago, when the majority lived on farms. But despite urbanization and the rise of corporate farming, the family farm--more than 77,000 of them at last count--is still a vital part of Iowa's identity. Fly over the state in summertime or drive across it in fall, when the headlights of tractors shine from the fields at night and golden mountains of corn are stacked around elevators, and it's easy to see that an enormous percentage is farmland--more than 85 percent, in fact. Kirk Murray's loving and endearing photographs make this guide the perfect companion for drives in the countryside in all seasons. They celebrate the rich activities and varied beauties of each season on the farm, from the starkness of winter whites to the pale and rich greens of spring and summer to the rust-reds and golds of fall. Murray's photos of sprouting corn at dawn, a summer sun shining on a farm pond, and a full moon over a silver silo echo Grant Wood and Vincent Van Gogh; his photos of tilling, planting, and harvesting are bright and energizing; his scenes of barnyards and fields and farmsteads are colorful and luminous; and his photos of farm animals are just plain fun. With eighty full-color photographs of the most common animals, activities, crops, and buildings that you can expect to see whenever you pass a family farmstead, Iowa Farm in Your Pocketwill be a treat for all newcomers to a state where corn and beans and hogs rule, for both urban and rural children and their parents, and for all those who want to revisit memories of growing up on a farm.